Practica obra Amsterdam Apartamentos (2018)
The present report describes the knowledge and experience compiled during the business practice which was carried out for a period of six months in the project of the building site of “Ámsterdam Apartamentos”, a housing construction project conformed by three towers which represent a construction area of 6000m², in charge of the construction company Soluciones Civiles S.A. During the development of the practice, progress was made in excavations of tower 2 and the beginning of the first apartment slab. The activities developed during the working day were always carried out under the supervision of the Resident Engineer, the reason of the that was because of the need of precision that the beginning of a structure requires.